COMPARATIVE CHARACTERISTICS OF ANTHROPOMETRIC INDICATORS IN ADOLESCENTS WITH DOWN SYNDROME (LITERATURE REVIEW) - Shukhrat J. Teshayev; Dilorom A. Ochilova (Central Asian Journal of Medicine, 2023)
When it is called the development and formation of a child's organism, its comprehensiveness: includes complex stages and periods of mental and physical maturation, the peculiarities of individual variability and its relationship with factors of the internal and external environment that determine the physical development of children and adolescents [1]. Physical development is a dynamic process of growth and maturation of a child at different age periods of childhood, which is considered one of the main indicators of the state of Health [3, 8].